The Welfare State and the Employment Problem - Lindbeck, Assar (American Economic Review, 1993)
Social security, provision of public sector services, job security legislation, minimum wages and centrally regulated (bargained) relative wages are important elements of the modern welfare state – each designed, often quite successfully, to enhance economic security and to redistribute income. The consequences of these policies for the unemployment issue are the topic of this paper.